THE EFFECTIVENESS OF PICTURE SERIES IN TEACHING NARATIVE TEXT; CASE STUDY IN SMA WACHID HASYIM - Ilda Adam Sari; Miftahul Huda; Sun'ul Fithon (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2017)
Writing is skill that needs a deep of thinking. In learning English writing is considered to be difficult, not only students but also the teacher feels that teaching wring is difficult. The activities of writing can apply through some of texts. As like descriptive text, Narrative text, Procedure text, spoofs text. Narrative text is the text telling about story or fable. The purpose of the narrative text is to entertain the listener or a reader (by the real story experience) or peculiar event and finished with ending. The problem in this research is: 1) The process of teaching writing by using picture series, 2) the effectiveness in teaching writing of narrative text by using picture series. The population in this research is 95 and the writer takes 25 students as sample that is in the A class. Then the data are analyzed in systematics way, to know the significance, based on the result of pre-test and post-test. From the result of analysis process teaching writing by using picture series is emphasized in grammar because most of the students feels difficult to arrange the sentences. Based on the result of t-test is checked from the critical value at the t- value at the level of significance 10 by db. 24, it means that the result of t- test 14,046242 is higher than t- table 14 at the level significant 10 by db. 24.